2021
DOI: 10.1038/s41431-021-00940-8
|View full text |Cite
|
Sign up to set email alerts
|

Routinization of prenatal screening with the non-invasive prenatal test: pregnant women’s perspectives

Abstract: Due to the favorable test characteristics of the non-invasive prenatal test (NIPT) in the screening of fetal aneuploidy, there has been a strong and growing demand for implementation. In the Netherlands, NIPT is offered within a governmentally supported screening program as a first-tier screening test for all pregnant women (TRIDENT-2 study). However, concerns have been raised that the test’s favorable characteristics might lead to uncritical use, also referred to as routinization. This study addresses women’s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
48
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(52 citation statements)
references
References 41 publications
3
48
1
Order By: Relevance
“…The main reason to accept screening was “seeking reassurance” and the main reason to decline was “every child is welcome”. The majority (87.7%) did not perceive societal pressure to test 104 . Aneuploidy serum screening in the USA has changed from 2012 to 2020 with fewer testing laboratories available, a shift toward larger laboratories, and a 2.5‐fold reduction in pregnancies tested because of the introduction of cell‐free DNA screening technology 105 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The main reason to accept screening was “seeking reassurance” and the main reason to decline was “every child is welcome”. The majority (87.7%) did not perceive societal pressure to test 104 . Aneuploidy serum screening in the USA has changed from 2012 to 2020 with fewer testing laboratories available, a shift toward larger laboratories, and a 2.5‐fold reduction in pregnancies tested because of the introduction of cell‐free DNA screening technology 105 …”
Section: Resultsmentioning
confidence: 99%
“…The majority (87.7%) did not perceive societal pressure to test. 104 Aneuploidy serum screening in the USA has changed from 2012 to 2020 with fewer testing laboratories available, a shift toward larger laboratories, and a 2.5-fold reduction in pregnancies tested because of the introduction of cell-free DNA screening technology. 105 First-trimester screening for pre-eclampsia is being offered more commonly.…”
Section: Prenatal Aneuploidy Screening Using Non-invasive Technologymentioning
confidence: 99%
“…There are also ongoing concerns that the noninvasive manner of this testing process will lead to it becoming routinely offered by providers and accepted by parents without receiving adequate information of possible outcomes [12], which in the setting of population screening for an expanded panel of de novo conditions raises concern. In the Netherlands, where NIPT is offered within a national prenatal screening program, women value high-quality counselling that emphasises informed decision-making based on personal values and freedom to choose [14]. Women who participated in the Dutch TRIDENT 2 study rejected the view that NIPT is a morally responsible screening test for disorders that can only be prevented by termination of pregnancy [15].…”
Section: Introductionmentioning
confidence: 99%
“…Van der Meij et al [ 3 ] and Garcia et al [ 4 ] have explored these issues in the Dutch context where NIPT is currently offered as a first-tier screening test as part of a nationwide implementation study (TRIDENT-2). Neither of these studies confirmed the aforementioned concerns about routinization.…”
mentioning
confidence: 99%